The amount of movement of the weight raised and its relationship with some Albyu kinmetekih variables to track weight , in the first section of the lifting of the jerk - Abdul Wahab, Safaa (Journal of Physical Education, 2014)
The objective of this research is to determine the amount of movement possessed by gravity during the lift and its relationship with Biomechanichal variables track dynamic behavior of a column of gravity to the elevation of jerk, which included a sample search on the four-class young people to countries (Turkey, Iran, Syria, Iraq) was adopted imaging Alfedoa side of the path of gravity (Trajectory) camera fast (210 r / s), and set the amount of movement for the elevation of order (jerk) and the adoption of the first part of which (Lift to the chest) was also identified Biomechanichal variables to track the movement of gravity and of symbols (H1, H3, H5, H7) and (D1, D2, D4) after conducting the statistical analysis out research results the following: There is a correlation significant between the variables (the amount of movement in the rise first, third and fifth) and the variables of track dynamic behavior of a column of gravity (H III, V and VII) also there is a correlation significant between the variables of the amount of movement rise in the first, third and fifth) and the variables to track motor column weight (deviation first, second and third) 97